Reconceptualizing water history of Chinese Central Asia: Hydraulic modeling of the early 1st mill. AD irrigation system at Mohuchahangoukou-4 (MGK4), Xinjiang, China. (October 2020) - Li, Yuqi; Storozum, Michael J.; Jia, Xin; Wang, Xin; Frachetti, Michael D.
Highlights: MGK-4 contains a 1 st . millennium AD spate irrigation system. Three-dimensional hydraulic modeling was used to study ancient irrigation systems. Irrigation technologies in ancient Xinjiang had diverse origins. Irrigation helped Central Asian mountain pastoralists farm in harsh environments. Abstract: Irrigation is a fundamental technology that has supported farming in Xinjiang, China, facilitating the region's long-term role as a bridge between East Asia and western Eurasia. The dominant narrative of Xinjiang's water history ties most evidence for ancient irrigation to immigrants from Inner China, mainly arriving during the Han (202 BCE-220 CE), Tang (618–907 CE), and Qing (1644–1912) dynasties. In this study, we provide an investigation of an early 1st mill. AD irrigation system at the Mohuchahangoukou-4 (MGK4) site in southern Xinjiang using hydraulic modeling. The results show that this system was most likely a sophisticated spate irrigation system that fundamentally differed in operational principles from those river-diversion systems built by contemporaneous or earlier immigrants from Inner China. Combining the new results with those of previous research, we conclude that the irrigation technologies used at MGK4 were either developed locally or were derived from areas west of modern-day Xinjiang. This conclusion poses the necessity for us to reconceptualize the development of ancient irrigation technologies in Xinjiang as a non-linear process, in which at least two branches coexisted for a considerable period. One of them was imported from Inner China, while the other either developed locally or was imported from western Central Asia and beyond. At least since the early 1st mill. AD, the newly identified foothill irrigation technology has enabled agro-pastoralists to grow crops on considerable scales outside major oases, which we argue provided them a key role in transcontinental communications along the Silk Roads of western China.